Utilisation of Athel Leaves to Improve the Unconfined Compressive Strength of Soil - Ahweedi, Mohammed; Muhmed, Asma; Elzaroug, Omer (Journal of Pure & Applied Sciences, 2024)
Athel Leaves (AL) are plentiful agricultural waste that might result in a detrimental effect on the environment owing to inadequate disposal. The purpose of this paper is to experimentally assess the impact of Athel leaves as a novel sustainable waste application on the unconfined compressive strength (UCS) of soil. For the purpose of fulfilling this main objective, five AL percentages (1%, 2%, 3%, 4% and 5% by dry weight of soil) and four curing periods (3, 7, 14 and 28 days) were selected. The failure pattern was also studied to better understand the ultimate behaviour of the improved soil. Assessment of the derived conclusions revealed that the inclusion of AL into soil enhanced the UCS. Careful inspection of the stress-strain relationships showed that inclusion of AL resulted in increased peak stress at large strains. Additionally, it was found that bulging and shear were the two patterns observed in this research. This study confirms the possibility of incorporating AL in geotechnical applications with significant environmental benefits.